The Uncovering Tax Avoidance Drivers in IDX Mining Firms 2019-2021: Financial Distress, Thin Capitalization, and CSR Disclosure Effects - Brenda Tandayu; Lintje Kalangi; Steven Josia Tangkuman (Ilomata International Journal of Tax and Accounting, 2023)
Indonesia's low tax ratio compared to other Asia-Pacific nations may indicate the presence of tax avoidance. The Tax Justice Network has revealed that corporations are the primary culprits of tax avoidance in Indonesia, with mining companies being among the examples of such practices that have been exposed. Related to this phenomenon, this study seeks to acquire factual evidence on how financial distress, thin capitalization and the disclosure of corporate social responsibility affect the tax avoidance among mining firms publicly listed on the IDX during the period of 2019 to 2021. By utilizing purposive sampling technique, this study successfully selected 18 companies, generating a total of 54 observational data that were used for analysis. To obtain the required data, this study relied on secondary sources such as audited financial statements, annual reports and/or sustainable reports. The main approach employed for analyzing the data and testing hypotheses in this study was multiple linear regression analysis. The findings of the study demonstrate that financial distress has a significant negative impact on tax avoidance. However, the study did not find statistically significant evidence to support the impact of thin capitalization and corporate social responsibility disclosure on tax avoidance.